A case of retrograde jejuno-duodenal intussusception caused by jejunal lipoma: a case report and review of literature - Law, Yi Ying; Ye, Lingxiang (International Surgery Journal, 2016)
Adult intussusception is a rare entity, comprising 5% of all cases of intussusception. The presentation of adult intussusception commonly varies, ranging from chronic abdominal pain to acute presentation mimicking symptoms of bowel obstruction. This report describes a case of retrograde jejuno-duodenal intussusception in a 48-year old healthy male with a history of several episodes of diffuse abdominal pain and an acute episode of melena of 3 days duration. Examination revealed a soft, nondistended abdomen with palpable mass at upper abdomen associated with tenderness on palpation. Computed tomography scan findings revealed a 10cm length of jejuno-duodenal intussusception likely secondary to a jejunal lipoma. Exploratory laparotomy revealed resolved intussusception secondary to a lipoma which was treated with segmental intestinal resection. In this case report, we describe a rare case of retrograde jejuno-duodenal intussusception caused by a jejunal lipoma and performed a literature review on retrograde intussusception.